Boganmeldelser - Larsson, Paul; Esdorf, Annette; Gosden, Patrick; Nielsen, Beth Grothe; Koch, Ida; Kristensen, Catharina Juul; Lomell, Heidi Mork; Brydensholt, Hans Henrik; Levin, Claes; Utriainen, Terttu; Kimpimäki, Minna; Gunnlaugsson, Helgi; et al. (Nordisk Tidsskrift for Kriminalvidenskab, 2000)
Intet resumé